Effect of the pentagram (PG) strategy of thinking to developing focus accuracy, psychological energy and achievement for junior archery players - Abbas, A. A. A.; Dahash, Y. M. (International Journal of Yogic, Human Movement and Sports Sciences, 2023)
The importance of research is also evident in raising the level of performance and achievement in the game of archery by teaching young people to perform based on the correct psychological aspect in terms of thinking, concentration, and raising psychological energy using correct education and the psychological educational strategy at the same time, which is the pentogram (PG) strategy.